Structural manipulation of aporphines via C10 nitrogenation leads to the identification of new 5-HT(7A)R ligands - Karki, Anupam (Bioorg Med Chem, 2020)
Aporphine alkaloids containing a C10 nitrogen motif were synthesized and evaluated for affinity at 5-HT(1A)R, 5-HT(2A)R, 5-HT(6)R and 5-HT(7A)R. Three series of racemic aporphines were investigated: 1,2,10-trisubstituted, C10 N-monosubstituted and compounds containing a C10 benzofused aminothiazole moiety. The 1,2,10-trisubstituted series of compounds as a group displayed modest selectivity for 5-HT(7A)R and also had moderate 5-HT(7A)R affinity. Compounds from the C10 N-monosubstituted series generally lacked affinity for 5-HT(2A)R and 5-HT(6)R and showed strong affinity for 5-HT(1A) or 5-HT(7A)R. Compounds in this series that contained an N6-methyl group were up to 27-fold selective for 5-HT(7A)R over 5-HT(1A)R, whereas compounds with an N6-propyl substituent showed a reversal in this selectivity. The C10 benzofused aminothiazole analogues showed a similar binding profile as the C10 N-monosubstituted series i.e. strong affinity for 5-HT(1A)R or 5-HT(7A)R, with selectivity between the two receptors being similarly influenced by N6-methyl or N6-propyl substituents. Compounds 29 and 34a exhibit high 5-HT(7A)R affinity, excellent selectivity versus dopamine receptors and function as antagonists in 5-HT(7A)R cAMP-based assays. Compounds 29 and 34a have been identified as new lead molecules for further tool and pharmaceutical optimization.